Characterization and influence of deformation microstructure heterogeneity on recrystallization. Issue 1 (July 2015) - Godfrey, A; Mishin, O V; Yu, T
Abstract: The microstructure resulting from plastic deformation of metals typically contains heterogeneity on several length scales. This is also true for samples deformed to large strains, where an important form of heterogeneity is in the variation in microstructural refinement by high angle boundaries. A methodology for quantifying this type of heterogeneity based on the identification of areas classified as low misorientation regions (LMRs) is described, and some parameters for quantification of both the extent and length scale of LMRs are presented. It is then shown how this approach can be used to investigate the early stages of recrystallization in samples deformed to large strains, by direct comparison of electron backscatter diffraction (EBSD) maps of the same area before and after annealing. Methods for estimation of the stored energy of deformation from EBSD data are also surveyed and the problems of each for quantification of the local variation in stored energy are discussed, where it is concluded that a method based on the summation of the contributions from individual boundary segments is considered to be the best suited at present for characterization of the local variation in stored energy on the scale of the dislocation boundary features.